Prosedur Pencatatan Perkawinan dan Perceraian di Negara Indonesia dan Malaysia Perspektif Hukum Islam - Fahmi Basyar (Program Pascasarjana Universitas Ibrahimy, 2017)
One phenomenon that emerged in the Islamic world in the 20th century is the family law renewal efforts undertaken by countries with Muslim majority. This was done in response to the dynamic development of society life. There are at least three points that is the objective of family law renewal in the Islamic world, as a law unification effort, raising the status of female, and responding to developments and demands to provide solutions to existing problems. A review of Act Number 1 in 1974